2007
DOI: 10.1080/03014220709510082
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of homing following translocation of long‐tailed bats (Chalinolobus tuberculatus) at Grand Canyon Cave, New Zealand

Abstract: Homing behaviour in the New Zealand long-tailed bat (Chalinolobus tuberculatus), a temperate insectivorous species, was investigated at Grand Canyon Cave, central North Island. A pilot study of nine adult male bats was conducted to determine whether use of the cave was regular enough for a homing study. Eight bats returned to the cave over the 3-week monitoring period, six on the night following release. Nine additional bats carrying radio transmitters were then released at three sites (three at each site) c. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
4
1
Order By: Relevance
“…data) or died soon after release. Results also contrast with other translocations and displacement homing experiments, where bats dispersed from their release sites (Davis 1966, Gunier & Elder 1971, Guilbert et al 2007. It is uncertain which of the release techniques (juvenile release, prerelease captivity and post-release supplementary resource provision) resulted in the different outcome, since they have been shown to independently contribute to decreased dispersal or increased survival elsewhere (e.g.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…data) or died soon after release. Results also contrast with other translocations and displacement homing experiments, where bats dispersed from their release sites (Davis 1966, Gunier & Elder 1971, Guilbert et al 2007. It is uncertain which of the release techniques (juvenile release, prerelease captivity and post-release supplementary resource provision) resulted in the different outcome, since they have been shown to independently contribute to decreased dispersal or increased survival elsewhere (e.g.…”
Section: Discussioncontrasting
confidence: 50%
“…data), although they may have died soon after release. Similarly, experiments testing the navigational ability of a number of bat species by translocating them outside their home ranges have shown that they frequently return to their source populations (Davis 1966, Gunier & Elder 1971, Guilbert et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…data, cited in Ruffell et al ., ). Bats, including long‐tailed bats, have the ability to home over long distances, decreasing the chance of founders establishing at a release site (Guilbert et al ., ). Furthermore, specific roosting requirements and probability of disease transmission may hinder establishment of bat populations following translocation relative to other taxa (Sedgeley & O'Donnell, ; Ruffell et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…For small distances, less than 8 mile, research has suggested that auditory cues (echolocation) are the primary mechanism for homing in bats [20]. Another recent study has shown that long-tailed bats (Chalinolobus tuberculatus) were successfully able to home to their cave after being released at distances from 5 km up to 20 km [21]. Bats have also been suggested to be capable of creating spatial maps in their memory of areas that are larger than their limited operating range of individual echolocation calls [22].…”
Section: Bats As a Model Of Bioinspirationmentioning
confidence: 99%